(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2015)
Attendance is one of the important factors that determine the students activity in any educational organizations. Taking attendance manually is considered as a huge task, even if, it was done using traditional methods such as barcode or smart card technologies leading to congestion and waste of time. The motivation of this papper is to simulate the wireless sensors network of a smart university (UOT) campus using OMNeT++ inorder to enhance the total power consumption of wireless nodes using several nodes scheduiling algorthim . The proposed system has been tested, and the results show that, the processing load of central server is decreased and the total transmission load over the wireless network also enhanced with value of 83%. Different experiments applied over distributed ZigBee wireless nodes in order to enhance network parameters .finally, the network parameters such as total power capacity and number of received packets had been improved using a linear queue node scheduling as proposed method.